2016
DOI: 10.1111/cbdd.12824
|View full text |Cite
|
Sign up to set email alerts
|

The C‐terminal sequences of porcine thrombin are active as antimicrobial peptides

Abstract: The C-terminal sequences of porcine thrombin encode a series of peptides with the characteristics of net positive charge and hydrophobicity, suggesting antimicrobial potential. In this study, we synthesized truncated C-terminal peptides to explore their antimicrobial potency and structure-activity relationship. The results showed that some peptides exerted antimicrobial activity against Gram-positive and Gram-negative bacteria, with selectivity for microbial membranes. The antimicrobial potency of the peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…6F, bacteriocin PA166 could permeate the bacterial cell membrane in a dose‐dependent manner. When the cell membrane permeated, the membrane potential dissipated and DiSC3(5) was released, leading to the enhancement of fluorescence (Lv et al ., 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6F, bacteriocin PA166 could permeate the bacterial cell membrane in a dose‐dependent manner. When the cell membrane permeated, the membrane potential dissipated and DiSC3(5) was released, leading to the enhancement of fluorescence (Lv et al ., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…When the cell membrane permeated, the membrane potential dissipated and DiSC3(5) was released, leading to the enhancement of fluorescence (Lv et al, 2016).…”
Section: Cytoplasmic Membrane Depolarizationmentioning
confidence: 99%
“…Currently, the NK-lysin has attracted considerable research interest since it has been reported to show a broad-spectrum antimicrobial activity and participate in the regulation of immune functions [ 20 ]. More than 12 kinds of porcine antimicrobial peptides have been found, including porcine thrombin, β-defensin-2, cecropin P1, and NK-lysin, which have broad-spectrum bactericidal effect on many microorganisms [ 32 , 33 ]. Among them, NK-lysin can directly combine the lipid part of lipopolysaccharide, resist various bacteria and fungi, such as E. coli , Bacillus megaterium , Acinetobacter acetate , and even dissolve some tumor cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…DiSC 3 -5, a membrane potential-sensitive fluorescent dye, was used to assess the ability of the peptides to disrupt the cytoplasmic membrane as previously described, [42]. Briefly, E. coli ATCC25922 in the mid-log phase was washed three times and diluted to an OD 600 of 0.05 with 5 mM HEPES buffer (containing 20 mM glucose and 100 mM KCl); then, the mixture of E. coli ATCC25922 and 0.5× MIC to 4× MIC peptides was mixed with diSC 3 -5 (final concentration of 0.4 µM) at 37 • C for 1 h. The fluorescence changes from 0 to 1500 s were recorded at the emission wavelength (λ = 670 nm) and excitation wavelength (λ = 622 nm) (Fluorescence Spectrophotometer, F4500, Hitachi, Tokyo, Japan).…”
Section: Cytoplasmic Membrane Depolarization Assaymentioning
confidence: 99%